THE DIFFERENCES OF INQUIRY TRAINING MODEL AND CONVENTIONAL ON STUDENTS LEARNING RESULT IN THE MATTER OF VIRUS IN CLASS X SMA NEGERI 1 LUBUKPAKAM - Nurhalimah Br Simbolon; Tonggo Sinaga (Universitas Negeri Medan, 2016)
This study aimed to find out the differences in student learning outcomes using model Inquiry Training with Conventional learning in the subject matter of the virus in class X SMA Negeri 1 Lubukpakam. This type of research is a quasi-experimental research. The sample in this study is the Experiment Class I (X4) and Class Experiment II (X3) each as many as 41 students. The results showed differences in learning outcomes of students taught using learning model Inquiry Training with conventional learning. Based on the average value of student learning outcomes in the classroom Inquiry Training at 84.15 with a standard deviation of 7.51, while the average value of the conventional classroom student learning outcomes at 80.24 with a standard deviation of 8.02. The big difference in learning outcomes can be proved by testing the hypothesis by using t-test and the level of confidence where tcount> ttable namely 2.277 > 1.664, which means in this study H0 while receiving Ha so it can be concluded that there is a difference in student learning outcomes significantly after being taught to use Training Inquiry learning model with conventional learning in the subject matter of the virus in class X SMA Negeri 1 Lubukpakam year study 2016/2017.Keywords: Model Inquiry Training, Learning Conventional and Virus.